Choroidal thickness does not predict visual acuity in young high myopes. (19th May 2016) - Gupta, Preeti; Cheung, Carol Y.; Saw, Seang‐Mei; Koh, Victor; Tan, Mellisa; Yang, Adeline; Zhao, Paul; Cheung, Chui Ming Gemmy; Wong, Tien Yin; Cheng, Ching‐Yu
Abstract: Purpose: To investigate the influence of choroidal thickness (CT) on visual acuity (VA) in young persons with extremely high myopia. Methods: We conducted a case–control study of young men with extremely high myopia and controls with emmetropia recruited from a mandatory medical eye review for employment purposes. Retinal and choroidal imaging was performed using enhanced depth imaging (EDI) spectral‐domain optical coherence tomography (SD‐OCT). Results: We included 105 extremely high myopic subjects with spherical equivalent (SE) ‐10 dioptre (D) or worse and 50 emmetropic subjects with SE less than 0.5 D. The mean SE was −11.56 ± 2.04 D (range, −10 to −23 D) for myopic group and 0.14 ± 0.25 D for emmetropic group. The mean age of included myopic and emmetropic subjects was 21.51 ± 1.22 years and 21.96 ± 0.89 years, respectively. In the univariate analysis, subfoveal CT was significantly associated with best‐corrected visual acuity (BCVA) ( β  = −0.039, p = 0.015). However, in the multiple linear regression analysis, after adjusting for SE and presence of any pathological myopia lesions such as posterior staphyloma, lacquer cracks or chorioretinal atrophy, subfoveal CT was not independently associated with BCVA (p = 0.937). Conclusion: Extremely high myopic eyes had thinner choroid, but CT was not an independent predictor of VA. Other factors related to myopia are likely responsible for the diminished VA in young extremely high myopic eyes.